Factors affecting the adoption and use of AVR technology in higher and tertiary education - Matsika, Cyncia; Zhou, Munyaradzi (Elsevier, 2022)
The research study assesses the factors that determine the adoption of Augmented and Virtual Reality (AVR) technology in Higher and Tertiary Education. In spite of the well-established potential benefits of AVR technology in education, it appears that most Higher and Tertiary Institutions have not holistically adopted it as a method of teaching and learning. Thus, it is important to investigate the reasons why AVR has not been adopted. Inductive qualitative research was conducted virtually with the aid of a questionnaire instrument. The Technology Acceptance Model (TAM) was used to establish the determinants for the adoption of AVR Technology. The research study found out that the main reasons for the lack of adoption of AVR technology were due to the lack of coordinating policies; lack of enabling infrastructures; perceived complexity of the use of AVR technology and a lack of a framework that guides the holistic as well as homogenous adoption of AVR technology in Higher and Tertiary Education. The research concluded that an AVR technology was necessary and should factor in the barriers to adoption. The study recommends inter-professional working of key players such as the Ministry of Higher Education (in endorsing an AVR technology model), the lecturers (using and encouraging AVR technology), and the students (active participation and use of AVR technology to learn). Prior to this study, the aspect of inter-professional working as a solution to the adoption and use of AVR in Higher and Tertiary Education had not been explored. However, more still needs to be done within Virtual Training and the development of an AVR model for teaching and learning.